Pembuatan Alat Ukur Kualitas Air Berbasis Arduino untuk Peningkatan Kompetensi Teknologi Siswa SMK - Tunjung Genarsih; Angga Dwinanda; Ardianto Syaifur Rohman; Sihmaulana Dwianto; Prisilia Angel Tantri (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
SMK Darul Hikmah faces challenges in enhancing students' technological competencies, particularly in applied technology and environmental problem-solving. This community service activity aims to improve students' technical skills through a Workshop "From Concept to Realization: Practical Arduino-Based Water Quality Measurement Tool Creation". The method used was project-based learning with 20% theory and 80% practice, complemented by pretest and posttest as achievement measurement tools. The workshop was attended by 21 students from technology skill competencies. Results showed significant improvement: 57% of participants were able to assemble and test sensors independently, 38% understood the material well, and 71% expressed high satisfaction with the activity. Additionally, 67% of participants were highly motivated to develop further Arduino and IoT-based projects. This activity proved effective in improving students' technical competencies in Arduino programming (C++), water quality sensor assembly (pH, TDS, turbidity), and understanding of environmental monitoring concepts relevant to industry needs in the Industrial Revolution 4.0 era.